Shifting Journalistic Ethics in the Internet Age, Case Study: Violation of Journalistic Ethics in Journalistic Products and Journalist Behavior in Online Media - Lestari, Rani Dwi (Komunikator, 2019)
The internet era has contributed greatly to the dynamic development of journalism. The consequences of the presence of the internet in journalism change at least two basic things, namely the presentation of journalistic products and the behavior of journalists. The internet has given rise to new media platforms, namely online media and changing information dissemination to be faster and more massive. The internet also affects journalist behavior in the field in the process of searching, processing and disseminating information. On the one hand, journalistic ethics as signs that regulate journalistic products and journalist behavior has shifted in the era of internet journalism. The Journalistic Code of Ethics is considered to only regulate the ethical side of conventional journalism practices and does not cover online journalism. This is what makes many violations of journalistic ethics in online media. This study aims to find out how the shift in journalistic ethics in online journalism. This research will also describe how forms of journalistic ethics violate in online media both in terms of journalistic products and journalist behavior. The results of this study are expected to provide input to the articles in the Journalistic Code of Ethics to be applied not only in the practice of conventional journalism but also online journalism.